Association of Early and Late Contrast-Associated Acute Kidney Injury and Long-Term Mortality in Patients Undergoing Coronary Angiography - Zhubin Lun; Jin Liu; Liwei Liu; Jingjing Liang; Guanzhong Chen; Shiqun Chen; Bo Wang; Qiang Li; Haozhang Huang; Zhidong Huang; Danyuan Xu; Yunzhao Hu; et al. (Journal of Interventional Cardiology)
Background. Contrast-associated acute kidney injury (CA-AKI) is a common complication in patients undergoing coronary angiography (CAG). However, few studies demonstrate the association between the prognosis and developed CA-AKI in the different periods after the operation. Methods. We retrospectively enrolled 3206 patients with preoperative serum creatinine (Scr) and at least twice SCr measurement after CAG. CA-AKI was defined as an increase ≥50% or ≥0.3 mg/dL from baseline in the 72 hours after the procedure. Early CA-AKI was defined as having the first increase in SCr within the early phase (<24 hours), and late CA-AKI was defined as an increase in SCr that occurred for the first time in the late phase (24–72 hours). The first endpoint of this study was long-term all-cause mortality. Kaplan–Meier analysis was used to count the cumulative mortality, and the log-rank test was used to assess differences between curves. Univariate and multivariate cox regression analyses were performed to assess whether patients who developed different type CA-AKI were at increased risk of long-term mortality. Results. The number of deaths in the 3 groups was 407 for normal (12.7%), 106 for early CA-AKI (32.7%) and 57 for late CA-AKI (17.7%), during a median follow-up period of 3.95 years. After adjusting for important clinical variables, early CA-AKI (HR = 1.33, 95% CI: 1.02–1.74, P=0.038) was significantly associated with mortality, while late CA-AKI (HR = 0.92, 95% CI: 0.65–1.31, P=0.633) was not. The same results were found in patients with coronary artery disease, chronic kidney disease, diabetes mellitus, and percutaneous coronary intervention. Conclusions. Early increases in Scr, i.e., early CA-AKI, have better predictive value for long-term mortality. Therefore, in clinical practice, physicians should pay more attention to patients with early renal injury related to long-term prognosis and give active treatment.